Palmistry: the mystery of destiny - "Chabra, Sunila" (Mumbai, 2011)
Palmistry is the cryptic code of life. A soul takes birth with his/her manual of destiny written on the hand. What an intriguing thought! Though we do not remember our past births, probably due to karmic amnesia, our brains store this information, in addition to the blueprint of our present lives. According to proven scientific theory, nerves carry messages from the brain to the hands. Palmistry believes that the nerves also carry the cryptic code of our destiny from the brain to the hands. Palmistry can trace its roots back to ancient India. The first section of this volume tells us how to interpret lines and signs on the palm using Hindu palmistry. Some of the ancient signs that are included here, appear for the first time in any book published on the subject. The second section is devoted to outlining the destiny paths of the rich and famous: Barrack obama, Vladmir Putin, Albert Einstein, Sonia Gandhi, Michael Jackson, Prince Charles, Nicole Kidman, Benazir Bhutto and Hillary Clinton. This book includes spiritual messages to help us understand the larger picture and move towards peace and happiness in the journey of life.
Keywords: Palmistry